Trade retaliation in a monetary-trade model - John Whalley; Jun Yu; Shunming Zhang (Center for Economic Studies and ifo Institute (CESifo), 2009)
We explore how outcomes of trade policy retaliation (Nash tariff games) are affected when trade simultaneously takes places geographically across countries and through time via financial intermediation. In such models deficits and surpluses in goods trade are endogenously determined, and retaliatory trade policy towards goods can affect these and monetary trade models show different retaliatory trade outcomes from conventional goods only models. We use a general equilibrium goods trade model which also captures trade through time in the form of inside money as used in macro literature on one good overlapping generations models. In this model the deficit or surplus of any country in goods trade is endogenous determined. Optimal trade policy differs from that in a conventional goods only trade model in that countries which run trade deficits in goods will have more strategic power through tariff policy (and surplus countries less) than in models with balanced trade. We calibrate such a model to China's trade with the rest of the world and explore two country tariff games using 2005 data. Results show the significant impacts on Nash outcomes of endogenizing the Chinese trade surplus in the model in this way.
Keywords: F13; 330; Inside money; general equilibrium; Nash equilibrium; numerical analysis; tariff rate; Retorsionsmaßnahme; Zolltarif; Außenwirtschaftstheorie; Allgemeines Gleichgewicht; Geld; Finanzintermediär; Overlapping Generations; Theorie; Zollpolitik; Spieltheorie; Nash-Gleichgewicht; China